Fostering Village Prosperity: Digital Innovations in Service Information and Uplifting UMKM Marketing Transforming Desa Balongdowo in Indonesia - Triwiyanto, Triwiyanto; Luthfiyah, Sari; Utomo, Bedjo; Hamzah, Torib (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2023)
In today's digital era, marketing trends are evolving along with increasingly sophisticated technological changes. Digital marketing comes as a new innovation where the marketing process of a product or service can be done through digital or internet. Digital marketing provides opportunities for businesses of various sizes and types of businesses that want to be marketed, while introducing their products to a wider market at a more affordable price. On the other hand, village development currently requires information technology to improve services to the community. website-based information systems can improve services to the community so that information to the community can be accessed easily and accurately. This Community Service activity is carried out to support the progress of Balongdowo Village through digital marketing and village information systems that can provide benefits to the community and local businesses. Target achievements in terms of Digital Marketing include the achievement of increased sales of processed kupang products and expansion of buyer reach. As well as the achievement in terms of Information System is the better-known profile and potential of Balongdowo village through the village website. Implementation in the field of Digital Marketing is done through seminars and mini workshops to Balongdowo villagers and MSMEs on how to register and market processed kupang products in e-commerce. Implementation in the field of Information Systems includes the creation of an information system portal in the form of a Balongdowo Village website. The method used in this Community services includes the implementation of Forum Group Discussion (FGD) for the initial understanding of the community regarding e-commerce. Followed by digital marketing training and evaluated through the buying and selling process in e-commerce. As for the field of Information Systems, FGD was also conducted, followed by a mini workshop on the operation of the Balongdowo Village Website Portal, as well as assistance in making multimedia documents and uploading them on the village website portal. And the evaluation can be seen in the development of the information system portal. Currently, Balongdowo Village already has a website, as well as the success of several business actors in Balongdowo Village who have accounts on Tokopedia, Shopee and Blibli. Digital marketing assistance provides benefits in improving the capabilities of the digital marketing team and strategy innovation. The creation of the Village Service Information System (SIPD) improved the efficiency, transparency and effectiveness of village services, and enabled better data management.